2003
DOI: 10.1002/mus.10534
|View full text |Cite
|
Sign up to set email alerts
|

Na+,K+‐ATPase concentration and fiber type distribution after spinal cord injury

Abstract: Complete spinal cord injury (SCI) is characterized, in part, by reduced fatigue-resistance of the paralyzed skeletal muscle during stimulated contractions, but the underlying mechanisms are not fully understood. The effects of complete SCI on skeletal muscle Na(+),K(+)-adenosine triphosphatase (ATPase) concentration, and fiber type distribution were therefore investigated. Six individuals (aged 32.0 +/- 5.3 years) with complete paraplegia (T4-T10; 1-19 years since injury) participated. There was a significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 31 publications
(50 reference statements)
3
31
3
Order By: Relevance
“…23 There is also a suggestion that spasticity contributes to the predominance of slow fibers in individuals with SCI. 40 Slow fibers are characterized by greater mitochondrial density compared to fast fibers. This could have resulted in partitioning of IMF towards oxidation in the HLI group rather than storage in the LLI group.…”
Section: Discussionmentioning
confidence: 99%
“…23 There is also a suggestion that spasticity contributes to the predominance of slow fibers in individuals with SCI. 40 Slow fibers are characterized by greater mitochondrial density compared to fast fibers. This could have resulted in partitioning of IMF towards oxidation in the HLI group rather than storage in the LLI group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested a preservation of contractile properties and/or an increased expression of slow twitch fibres in muscle that experiences a significant degree of spasticity after SCI. 15,16 Furthermore, Stein et al 17 suggested that if spasticity occurs more frequently in the extensor muscles (such as the soleus), the tibialis anterior muscle would be placed in a stretched position, thus preserving the torque-generating capacity of that muscle. In contrast, the extensor muscles would be exposed to more shortened positions because of both the prolonged sitting Table 3 M-wave amplitude (mV) at various joint angles for able-bodied (AB) and spinal cord-injured (SCI) participants position in a wheelchair and the repeated bouts of spasticity.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In addition, although functional electrically stimulated (FES) exercise has shown great promise as a cardiovascular stimulus, [5][6][7] it carries the risks of burns to the skin, autonomic dysreflexia and bone fracture, and further, stimulated contractions may not be evoked in those with lower motor neuron injuries. 8 The cardiovascular benefit of FES exercise may also be limited as individuals with SCI are more prone to muscle fatigue, [9][10][11] and may only perform such exercise for relatively short durations. 11 In the last decade, body-weight supported treadmill training (BWSTT) has shown promise as a means of enhancing gait recovery in SCI individuals with partially spared motor function, [12][13][14][15][16] but not in those with motorcomplete SCI.…”
Section: Introductionmentioning
confidence: 99%